From Sentence Anxiety to Paragraph Confidence: A Pedagogical Study of Arabic Writing Development - Menik Mahmudah; Afaf Fudhla; Nurul Azira; Juharoh; Mustahar Ali Wardana (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2026)
Writing anxiety remains a persistent challenge in Arabic language education, often hindering learners’ engagement and development in maharah kitābah. This study investigates the effectiveness of paragraph-based writing instruction in transforming learners’ writing experiences from sentence-level anxiety to paragraph-level confidence. Employing a qualitative pedagogical research design, the study was conducted with intermediate-level learners of Arabic and utilized classroom observations, learners’ written paragraphs, and semi-structured interviews as primary data sources. The findings indicate that paragraph-focused instruction reduces writing anxiety by lowering cognitive load and providing a psychologically safe space for meaning construction. Learners reported increased confidence, greater willingness to write, and higher engagement during writing activities. Rather than emphasizing immediate grammatical accuracy, paragraph-based tasks encouraged sustained participation, revision, and linguistic experimentation. The study concludes that paragraph-by-paragraph instruction serves as an effective pedagogical strategy for addressing affective barriers in Arabic writing development. By integrating cognitive and emotional considerations into instructional design, this research contributes to the advancement of learner-centered Arabic writing pedagogy.